Aquaporins and CO2 diffusion across biological membrane - Chen, Junyu; Yue, Ke; Shen, Lulu; Zheng, Chuncui; Zhu, Yiyong; Han, Kun; Kai, Lei (Frontiers in Physiology, 2023)
Despite the physiological significance of effective CO2 diffusion across biological membranes, the underlying mechanism behind this process is not yet resolved. Particularly debatable is the existence of CO2-permeable aquaporins. The lipophilic characteristic of CO2 should, according to Overton’s rule, result in a rapid flux across lipid bilayers. However, experimental evidence of limited membrane permeability poses a challenge to this idea of free diffusion. In this review, we summarized recent progress with regard to CO2 diffusion, and discussed the physiological effects of altered aquaporin expression, the molecular mechanisms of CO2 transport via aquaporins, and the function of sterols and other membrane proteins in CO2 permeability. In addition, we highlight the existing limits in measuring CO2 permeability and end up with perspectives on resolving such argument either by determining the atomic resolution structure of CO2 permeable aquaporins or by developing new methods for measuring permeability.